The Biocontrol Efficacy of Streptomyces pratensis LMM15 on Botrytis cinerea in Tomato. (28th November 2017) - Lian, Qinggui; Zhang, Jing; Gan, Liang; Ma, Qing; Zong, Zhaofeng; Wang, Yang
Abstract : LMM15, an actinomycete with broad spectrum antifungal activity, was isolated from a diseased tomato leaf using the baiting technique. A phylogenetic tree analysis based on similarity percentage of 16S rDNA sequences showed that the bacterium was 97.0% affiliated with the species Streptomyces pratensis . This strain was therefore coded as S. pratensis LMM15. The ferment filtrate of LMM15 had ability to inhibit mycelia growth of Botrytis cinerea and reduce lesion expansion of gray mold on detached leaves and fruits. In greenhouse experiments, both the fresh and dry weights of tomato seedlings were significantly increased with the increased concentrations of total chlorophyll. The incidence of tomato gray mold decreased by 46.35%; this was associated with the increase of proline content and malondialdehyde (MDA) and the changes in defense-related enzymes on tomato leaves when the strain was sprayed on the tomato leaves 24 h prior to inoculation with pathogens. This study showed that the strain S. pratensis LMM15 could be a potential agent for controlling tomato gray mold.